The Application of Design Thinking in Differential Learning to Develop Students' Critical Thinking Ability - Ayu Endah Pratiwi; Muhtarom; Aryo Andri Nugroho (JTP - Jurnal Teknologi Pendidikan, 2025)
This study examines the effectiveness of implementing a design thinking approach in differential learning to enhance students’ critical thinking skills. A quasi-experimental method with a pretest–posttest control group design was employed. The participants consisted of 60 undergraduate students enrolled in a Differential Calculus course, who were assigned to an experimental group (n = 30) receiving design thinking-based instruction and a control group (n = 30) receiving conventional instruction. The research instrument was an essay-based critical thinking test developed according to five indicators: interpretation, analysis, evaluation, inference, and explanation. Data were analyzed using descriptive statistics and an independent samples t-test. The findings revealed a statistically significant difference in critical thinking skills between the experimental group (M = 83.67) and the control group (M = 68.43), with p < 0.001. The experimental group achieved an N-Gain score of 0.64, categorized as moderate to high and substantially higher than the control group’s N-Gain of 0.32. Furthermore, Cohen’s effect size was 2.41, indicating a very large effect. Improvements were observed across all critical thinking indicators, with the analysis indicator demonstrating the greatest gain (a mean difference of 16.67 points). In conclusion, design thinking-based learning is effective in enhancing students’ critical thinking skills in differential calculus and represents a promising alternative instructional approach for university-level mathematics education.